A LARGE FOREIGN BODY IN THE TRACHEA (SEWING NEEDLE) - P. D. Pryanikov; D. M. Mustafayev (Неотложная медицинская помощь, 2017)
The authors present a case study: an unusual foreign body (sewing needle) in the trachea. Despite the large size and unusual shape of a foreign body, we managed to remove it through the airways with rigid upper traheobronchoscopy, avoiding complications.